SAR110894, a potent histamine H3‐receptor antagonist, displays disease‐modifying activity in a transgenic mouse model of tauopathy. Issue 4 (2nd November 2016) - Delay‐Goyet, Philippe; Blanchard, Véronique; Schussler, Nathalie; Lopez‐Grancha, Mati; Ménager, Jean; Mary, Véronique; Sultan, Eric; Buzy, Armelle; Guillemot, Jean‐Claude; Stemmelin, Jeanne; Bertrand, Philippe; Rooney, Thomas; et al.
Abstract: Introduction: Tau hyperphosphorylation and neurofibrillary tangles are histopathologic hallmarks of tauopathies. Histamine H3‐receptor antagonists have been proposed to reduce tau hyperphosphorylation in preclinical models. Methods: We evaluated the ability of SAR110894, a selective histamine H3‐receptor antagonist, to inhibit tau pathology and prevent cognitive deficits in a tau transgenic mouse model (THY‐Tau22). Results: SAR110894 treatment for 6 months (but not 2 weeks) in THY‐Tau22 mice decreased both tau hyperphosphorylation at pSer396‐pSer404 (AD2 signal) in the hippocampus and the number of AT8 (pSer199/202‐Thr205) positive cells in the cortex and decreased the formation of neurofibrillary tangles in the cortex, hippocampus, and amygdala. Macrophage inflammatory protein 1‐alpha messenger RNA expression was decreased in the hippocampus. SAR110894 also prevented episodic memory deficits, and this effect was still detected after treatment washout. Discussion: Long‐term SAR110894 treatment could have potential disease modifying activity in neurodegenerative tauopathies.